Neurological prognostication tools in out‐of‐hospital cardiac arrest patients in Danish intensive care units from 2005 to 2013. Issue 10 (26th June 2018) - Winther‐Jensen, M.; Hassager, C.; Lassen, J. F.; Køber, L.; Torp‐Pedersen, C.; Hansen, S. M.; Lippert, F.; Kragholm, K.; Christensen, E. F.; Kjaergaard, J.
Abstract : Background: Neurological prognostication is an essential part of post‐resuscitation care in out‐of‐hospital cardiac arrest (OHCA). This study aims to assess the use of computed tomography (CT) and magnetic resonance imaging (MR) of the head, electroencephalography (EEG), and somatosensory evoked potentials (SSEP) in neurological prognostication in resuscitated OHCA patients and factors associated with their use in Danish tertiary and non‐tertiary centers from 2005 to 2013 and associations with outcome. Methods: We used the Danish Cardiac Arrest Registry to identify patients ≥18 years of age admitted to intensive care units due to OHCA of presumed cardiac etiology. CT 0‐20 days and MR, SSEP, and EEG ≥2‐20 days post OHCA were considered related to prognostication. Incidence and factors associated with procedures were assessed by multiple Cox regression with death as competing risk. Results: Use of CT, MR, EEG, and SSEP increased during the study period (CT: 51%‐67%, HRCT : 1.06, CI: 1.03‐1.08, MR: 2%‐5%, P = .08, EEG: 6%‐33%, HREEG : 1.25, CI: 1.19‐1.30, SSEP: 4%‐15%, HRSSEP : 1.23, CI: 1.15‐1.32). EEG and SSEP were more used in tertiary centers than non‐tertiary (HREEG : 1.86, CI: 1.51‐2.29, HRSSEP : 4.44, CI: 2.86‐6.89). Use of CT, SSEP, and EEG were associated with higher 30‐day mortality, and MR was associated with lower (HRCT : 1.15, CI: 1.01‐1.30, HRMR : 0.53, CI: 0.37‐0.77, HRSSEP : 1.90, CI: 1.57‐2.32, HREEG : 1.75, CI: 1.49‐2.05). Conclusion: Use of neurological prognostication procedures increased during the study period. EEG and SSEP were more used in tertiary centers. CT, EEG and SSEP were associated with increased mortality.